Disinhibited Revenge – An fNIRS Study on Forgiveness and Cognitive Control - Maier, Moritz Julian; Rosenbaum, David; Haeussinger, Florian Benedikt; Brüne, Martin; Fallgatter, Andreas Jochen; Ehlis, Ann-Christine (Frontiers in Behavioral Neuroscience, 2019)
The ability to reconcile is a key factor for a cooperative and successful life. Among the manifold factors that impact on how people negotiate social contracts, poor cognitive control (which is inversely linked to impulsivity) may exert negative effects on forgiveness. To investigate the neurobiological basis of this proposition, subjects with high vs. low impulsivity scores completed an ultimatum game (UG) and a dictator game (DG). First the participants played an UG where they had to accept or reject offers from fair or unfair opponents. Afterwards, the roles changed, and a DG was played. Here, subjects had the opportunity to forgive or take revenge towards the unfair opponents by the allocation of a fair/unfair amount of money. During this task, activity of the dorsolateral prefrontal cortex (DLPFC) was assessed via functional near-infrared spectroscopy (fNIRS). Highly impulsive subjects were significantly more revenge-seeking than low impulsive individuals. This behavioral difference was reflected in the activation pattern of the left DLPFC, where higher activation in trials with unfair opponents was found, but only in the highly impulsive group. This result is discussed as an indicator for a more revenge-driven behavior in highly impulsive individuals, as activity in the left DLPFC is associated with retaliation.